Chemical composition, in vitro and in silico approaches of the relaxant effect of the jejunum using Thymus algeriensis Boiss. and Reut essential oil - Leila Beyi; Mohamed Marghich; Ouafa Amrani; Ahmed Karim; Tarik Harit; Mohammed Aziz (Elsevier, 2023)
Background: Gastrointestinal problems are among the most common diseases in Morocco people, who frequently use aromatic and medicinal plants to eliminate these problems. Thymus algeriensis is one of these plants widely used to treat gastrointestinal problems. This research aimed to identify the phytochemical compounds present in Thymus algeriensis essential oil (TaEO), assess its acute toxicity, and investigate its potential myorelaxant and antispasmodic effects. Methods: In vitro experiments were conducted on rat and rabbit jejunum using an isotonic transducer and in silico docking calculations were conducted on l-type voltage-gated Ca2+and muscarinic receptor active sites. Results: The GC-MS analysis of TaEO revealed the presence of 11 compounds, with 89.77 % of the compounds identified being oxygenated monoterpenes, among which Thujone dominates the composition with 32.89 %. The administration of TaEO did not produce any observable signs of toxicity or mortality at 1 g/Kg.bw. TaEO exhibit a dose-dependent decrease in the basal contractions of the rabbit jejunum with an IC50 value of 5.66 ± 1.88 µg/mL. In addition, TaEO induced an antispasmodic effect on KCl and CCh-induced contractions in the rat jejunum. The inhibitory effect demonstrated are similar to those produced by a non-competitive antagonist of voltage-dependent calcium channel and cholinergic receptors. These results are boosted by the docking study when we showed that Thujone could bind to the active site of muscarinic receptor and, l-type voltage-gated Ca2+ with a binding energy equal to -59.401 and, -47.441 Kcal/mol respectively. Conclusions: These results provide strong confirmation for the traditional use of Thymus algeriensis in Moroccan as an effective antispasmodic remedy and give a new lead to find a phytomedicament against gastrointestinal problems.